New XMM–Newton observations of faint, evolved supernova remnants in the Large Magellanic Cloud. Issue 3 (24th March 2022) - Kavanagh, P J; Sasaki, M; Filipović, M D; Points, S D; Bozzetto, L M; Haberl, F; Maggi, P; Maitra, C
ABSTRACT: The Large Magellanic Cloud (LMC) hosts a rich population of supernova remnants (SNRs), our knowledge of which is the most complete of any galaxy. However, there remain many candidate SNRs, identified through optical and radio observations where additional X-ray data can confirm their SNR nature and provide details on their physical properties. In this paper, we present XMM–Newton observations that provide the first deep X-ray coverage of ten objects, comprising eight candidates and two previously confirmed SNRs. We perform multifrequency studies using additional data from the Magellanic Cloud Emission Line Survey (MCELS) to investigate their broad-band emission and used Spitzer data to understand the environment in which the objects are evolving. We confirm seven of the eight candidates as bona-fide SNRs. We used a multifrequency morphological study to determine the position and size of the remnants. We identify two new members of the class of evolved Fe-rich remnants in the Magellanic Clouds (MCs), several SNRs well into their Sedov-phase, one SNR likely projected towards a H ii region, and a faint, evolved SNR with a hard X-ray core which could indicate a pulsar wind nebula. Overall, the seven newly confirmed SNRs represent a ∼10-per cent increase in the number of LMC remnants, bringing the total number to 71, and provide further insight into the fainter population of X-ray SNRs.